2000
DOI: 10.1007/s002560050592
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of clear cell sarcoma (malignant melanoma of the soft parts): a multicenter correlative MRI-pathology study of 21 cases and literature review

Abstract: nal intensities on T1-and T2-weighted images, contrast enhancement, relationship with adjacent fascia or tendon, secondary bone involvement, and intratumoral necrosis. In 19 cases the pathology findings were available for review and for a comparative MR-pathology study.Results. On T1-weighted images, lesions were isointense (n=3), hypointense (n=7) or slightly hyperintense to muscle (n=11). Immunohistochemical examination was performed in 17 patients. All 17 specimens showed positivity for HMB-45 antibody. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 22 publications
1
59
0
3
Order By: Relevance
“…On MRI clear cell sarcomas usually present as well-circumscribed lesions with variable SI on T1WI and T2WI. About 50% of tumors are slightly hyperintense to muscle on T1WI, probably due to the presence of melanin, and markedly hyperintense to muscle on T2WI [34]. Hourani et al suggested that clear cell sarcoma should be suspected in a lesion which displays high SI on all sequences, including fat-sat techniques [35].…”
Section: Synovial Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…On MRI clear cell sarcomas usually present as well-circumscribed lesions with variable SI on T1WI and T2WI. About 50% of tumors are slightly hyperintense to muscle on T1WI, probably due to the presence of melanin, and markedly hyperintense to muscle on T2WI [34]. Hourani et al suggested that clear cell sarcoma should be suspected in a lesion which displays high SI on all sequences, including fat-sat techniques [35].…”
Section: Synovial Sarcomamentioning
confidence: 99%
“…As clear cell sarcomas are often well-defined and homogeneous and rarely show bone destruction or necrosis, they are often misdiagnosed as benign lesions [10,31,[33][34][35][36] (Fig. 8).…”
Section: Synovial Sarcomamentioning
confidence: 99%
“…The tumours are usually intimately associated with fascial or tendoaponeurotic structures but may regularly involve the subcutis and dermis by direct extension. Radiologically the lesion is often mistaken for a benign process (De Beuckeleer et al, 2000). CCS is characterized by repeated local recurrence and, with time, metastasizes primarily to lymph nodes, the lungs and bone; 5 and 10 year survival is variable but is in the order of 50% and 10 -20%, respectively.…”
mentioning
confidence: 99%
“…Melanin has paramagnetic effects, resulting in shortening of T1 and T2 and thereby a high signal intensity on T1-weighted images and a low signal intensity on T2-weighted images. High signal on T1-weighted images can be used to distinguish a clear cell sarcoma from most other soft tissue tumors that lack the presence of melanin [1]. However, increased intensity on T1-weighted images is certainly not pathognomonic for melanin, since it also indicates the presence of fat, blood, or certain stages of proteinaceous material.…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…Conventional radiographic examination shows a noncalcified mass and is noncontributory in most cases [1,6,8]. Involvement of underlying bone is rare but has important clinical implications when present [2].…”
Section: Discussion and Treatmentmentioning
confidence: 99%